Commentary on “MiRNA Expression Analysis of Pretreatment Biopsies Predicts the Pathological Response of Esophageal Squamous Cell Carcinomas to Neoadjuvant Chemoradiotherapy” - Derouet, Mathieu; Darling, Gail E. (Translational Cancer Research, 2017)
Esophageal cancer has now become the 8th most common cancer and the 6th most common cause of death in the world (1). In a recent publication on neoadjuvant therapy in esophageal adenocarcinoma patients (2) tumor stage after neoadjuvant therapy predicted survival after surgery, however some patients do not respond to neoadjuvant therapy and thus their definitive treatment is delayed without benefit. Unfortunately even those who have a complete pathologic response may still die of metastatic disease. Identification and validation of molecular/biological markers to predict response to therapy would be of major benefit to patients and their doctors.